2018
DOI: 10.1155/2018/7360147
|View full text |Cite
|
Sign up to set email alerts
|

The DNA of Bacteria of the World Ocean and the Earth in Cosmic Dust at the International Space Station

Abstract: Cosmic dust samples from the surface of the illuminator of the International Space Station (ISS) were collected by a crew member during his spacewalk. The sampler with tampon in a vacuum container was delivered to the Earth. Washouts from the tampon's material and the tampon itself were analyzed for the presence of bacterial DNA by the method of nested PCR with primers specific to DNA of the genus Mycobacteria, DNA of the strains of capsular bacteria Bacillus, and DNA encoding 16S ribosomal RNA. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…We conclude by remarking that the discovery of Earth-like microorganisms on the exterior of the International Space Station by Grebennikova et al [7], if confirmed, gives strong credence to their introduction to the geospace environment from outside the Earth rather than from the Earth's surface. Only an infinitesimal part of the 100 of tonnes of meteoritic and cometary dust entering the Earth on a daily basis needs to be in the form of bacteria to explain their result.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…We conclude by remarking that the discovery of Earth-like microorganisms on the exterior of the International Space Station by Grebennikova et al [7], if confirmed, gives strong credence to their introduction to the geospace environment from outside the Earth rather than from the Earth's surface. Only an infinitesimal part of the 100 of tonnes of meteoritic and cometary dust entering the Earth on a daily basis needs to be in the form of bacteria to explain their result.…”
mentioning
confidence: 61%
“…Except during times of exceptionally energetic events such as powerful volcanic eruptions or (much more rarely) asteroid or comet impacts, dust from the surface cannot be naturally lofted into the stratosphere and above. The recent report of bacteria found at the orbit of the International Space Station (ISS) at 400km altitude is a counter-example that needs to be understood [7]. In this note we discuss the possibility of electric fields contributing to the transport of charged bacteria and dust from lower levels in the atmosphere into the ionosphere; we show that they are too small to have any significant effect.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Dust and sand from deserts, due to storms, can travel long distances even between continents and represent a vehicle for the dispersion of microorganisms, including NTM [247][248][249]. Also, mycobacterial DNA have been found in cosmic dust [250].…”
Section: (B) Soil and Dust Particlesmentioning
confidence: 99%
“…They are blank vacuoles, air-filled cavities within the sphere of knowledges-the unexplored territories; the issues and scientific fields which we have avoided or overlooked or simply had to pass due to a lack of either understanding; e.g., [12], or which we have avoided due to lack of methods for investigation, such as the enigmatic plasma vortices described by Levengood and Talbot in 1999 [13]. Alternatively, they arise from scientific questions preliminarily approached in theory, and only much later investigated with modern methods; e.g., the theory of panspermia originally presented in 1908 by Arrhenius [14] and revived a century later [15,16].…”
Section: The Search For Truthmentioning
confidence: 99%